Entrepreneurship Interests Students Viewed From Internship Experience and Role Of Teachers - Nurhuda Nurhuda; Soenarto Soenarto (Journal of Educational Science and Technology (EST), 2018)
This study aims to reveal the experience of internship and the role of teachers in the interests of student entrepreneurship. This study uses the ex-post facto method with a quantitative approach. The study population was vocational students in the Technical and Informatics Expe rtise Program in Buol District, which was precisely 160 students. The number of research samples is 113 students using proportional random sampling techniques. Data collection uses questionnaires. Data analysis used multiple regression analysis. The results showed that partially the internship experience (24.19%) and the role of the teacher (13.61%) had a positive and significant influence on the interest in entrepreneurship. While simultaneously the two variables are insightful for entrepreneurship interests of 37.8%. These results indicate that the experience of internship and the role of teachers are more so that it can produce vocational graduates not only ready to work but also able to entrepreneurship.